HUBUNGAN STATUS GIZI DENGAN HASIL PEMBELAJARAN PENJASORKES SISWA KELAS V SDN 007 PILAU BIRANDANG KECAMATAN KAMPAR TIMUR KEBUPATEN KAMPAR - Jasmawati '; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the researcher’s observation of students in class V of SDN 007 Pulau Birandang Kampar Timur District of Kampar. Researcher found the quality of learning outcomes of sport education still low caused to the lack of student motivation in sport education learning, environmental influences, physical fitness and nutritional status so that no spirit in sport education learning. Evident from learning outcomes still below average or below standars that class rise to minimal completeness criteria. The purpose of this research is to see the correlation of the nutritional status with the learning outcomes of student in class V of SDN 007 Pilau Birandang Kampar Timur District of Kampar. Population in this research are all students in class IV, V and VI amount 84 people. Based on population that is large and within the limits the researchers set the half population is used as a sample (purposive sampling). The study sample is all student in class V as many as 32 people. Research instrument used were the nutritional test that weigh student with scales and measuring height in the from of units of length are meters and learning outcomes test from raport outcomes. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : that is result obtained from student in class V of SDN 007 Pilau Birandang Kampar Timur District of Kampar. Shows that there is a correlation of the nutritional status with the learning outcomes, which shows correlation rhitungrhitung (0,003) < rtabel (0,355). For the results of the nutritional status as classified in the category of very thin.Key word : Nutritional Status, Learning Outcomes